Clinical Features, Surgical Treatment, and Long-Term Outcome of a Multicenter Cohort of Pediatric Moyamoya - Zheng, Jun; Yu, Le-Bao; Dai, Ke-Fang; Zhang, Yan; Wang, Rong; Zhang, Dong (Frontiers in Neurology, 2019)
Objective: To investigate the clinical features, long-term outcomes and prognostic predictors of a multicenter cohort of children with moyamoya disease. Methods: A series of 303 consecutive pediatric MMD were screened in this study. The clinical characteristics were retrospectively collected, and long-term outcomes was evaluated. Logistic regression analyses were performed to determine the prognostic predictors for clinical outcome. Results: The mean onset age at diagnosis was 9.4 years. Sex ratio (girl to boy) was 1.1:1. Of 303 patients, 13 patients underwent different surgical modalities in bilateral hemispheres, and 8 patients failed to follow-up were excluded. Therefore, 282 patients were analyzed, including 17 patients underwent combined bypass (CB), 47, direct bypass (DB), 150, indirect bypass (IB), and 68, conservative treatment. Recurrent stroke events were observed in 35 patients (12.4%). Kaplan-Meier analysis demonstrated that there was no significant difference in either the ischemia or hemorrhage-free time between different surgical modalities (p = 0.667 and 0.791, respectively). Otherwise, longer ischemia-free time was observed in surgical group than conservative groups (p=0.004). In addition, 82.7% (177/214) patients underwent surgical treatment obtained good outcomes (mRS 0-1) which was significantly higher than the rate of patients underwent conservative treatment (52.9%, 36/68, p<0.001). The rate of patients with improved symptoms was also significantly different (93.0% vs 16.2%, p<0.001). Otherwise, no significant difference was observed in rate of good outcomes, disability and improved symptoms between different surgical modalities. Logistic regression analyses revealed that postoperative ischemic events were the only risk factor associated with unfavorable clinical outcome (OR, 3.463; 95% CI, 1.436– 8.351; p=0.006). Conclusion: CB, DB, and IB have similar effects on long-term clinical outcome in pediatric moyamoya, but surgical revascularization is superior than conservative treatment. Postoperative ischemic events were confirmed as the prognostic factor associated with unfavorable clinical outcome.